AN ECONOMIC ANALISYS FOR PRICING POLICY AND POLICY OF FORIGEN TRADE OF AGRICULTURAL SECTOR IN IRAQ DURING 2003-2013 - & Mohammed, Al-Badri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
There is no doubt that Agricultural Policy is the main responsible for the degrading in Agricultural sector in Iraq during the period 2003-2013, and that was very clear from magnitude of indicators because of little sharing of each of agricultural product in GDP  because it was (9.38%) in average during the study period and the annual changing of it was negative (-5.82%), and there is increasing in deficit of trade balance in Agriculture during the study period about (4185.73) million US$, and the percentage of agricultural exports from total exports was (0.14%) in average only. The foreign trade policy in Agricultural products also cannot determine map of Revealed Comparative Advantage (RCA) of Agricultural products and crops. The study showed that there is continuous deficit in agricultural price policy because the agricultural producer is still receive prices for strategically crops less than world prices and that was showed by Net Nominal Protection Coefficients (NNPC) and although of the improvement than before 2003 but it is not paralleled with importance of Agricultural sector.